Automatic recognition of a car license plate using color image processing - Eun Ryung Lee; Pyeoung Kee Kim; Hang Joon Kim (Image Processing, 1994 International Conference on, 1994)
An automatic recognition method of a car license plate using color image processing is presented. At first, background colors of a plate are extracted from an input car image. A neural network is used for more stable extraction. To find a plate region, a fixed ratio of horizontal and vertical length of a plate is used. To recognize characters in a plate, template matching and postprocessing techniques are used. Since the proposed method does not depend on line information of a plate it is very robust to boundary deformation. Also, this method is strong enough to deal with a car's image which has many similar regions with a plate.< >